Balancing generosity and critique: reflections on interviewing young men and implications for research methodologies and ethics. (December 2020) - Elliott, Karla; Roberts, Steven
Feminist research methodologies have challenged power imbalances in qualitative interviews and gendered inequalities more broadly. We explore the methodological and ethical complexities of, and implications for, doing feminist research with young men. We draw on two studies in which narrative interviews with young men were conducted: one in 2014 and 2015 with 28 middle-class men between the ages of 20 and 31 living in Australia and Germany; and one a longitudinal study beginning in 2009 in the south-east of England with 24 working-class men between the ages of 18 and 24. We explore the production of narratives in interviews with young men, rapport-building, and interactional issues. Balancing generosity and critique emerges as a key ethical and methodological consideration for research conducted with young men. We suggest that negotiating the tensions of this balance can hold key possibilities for research and for proliferating alternative modes of masculinity.